Degree of namatode residence in rosemary on meloidogyne specie and related mechanism of residence - Shalang, Lehlogonolo Quecious (My University, 2023)
Tropical root-knot nematodes, Meloidogyne enterolobii, M. incognita and M. javanica, are highly damaging and difficult pests to manage in agricultural crops. The use of resistant cultivars had been the most promising strategy, which is currently among the proposed alternative nematode management strategies when appropriate cultivars are available in the management of nematode population densities. However, the main challenge associated with the estimation of the degree of nematode resistance is the absence of consistent guidelines for testing resistance. In order to identify plants with a source of resistance to Meloidogyne species, usually specific protocols are employed. Current methods for assessing resistance, such as the reproductive factor (RF), egg-mass index (EI), gall index (GI) and index of reproduction (IR), have associated limitations. The concept of relative susceptibility (rs) is increasingly used as a standardised quantitative method for testing the degree of nematode resistance. Therefore, the objective of this study was to determine whether rs of rosemary to tomato for M. enterolobii, M. incognita and M. javanica would either be above one or affect relative accumulation of selected mineral nutrient elements. Rosemary cuttings and tomato seedlings were raised in polystyrene trays containing Hygromix-T and transplanted into 20-cm diameter plastic pots containing steam-pasteurised soil. At two weeks after transplanting, plants were inoculated with 250 eggs of each Meloidogyne species, arranged in a randomised complete block design, replicated 10 times. Data were collected at 56 days after inoculation using maceration and blending method. Relative susceptibility, expressed as the ratio of final egg population density of a nematode population on a test variety (unknown resistance) compared to the population density of a standard reference variety (susceptible) was used for assessing the relative susceptibility of rosemary to cv. tomato 'Floradade'. Generally, since root sizes of different plants differ, nematodes in test plants were first standardised using reproductive potential (RP = total Pf/ g fresh roots) and when rsɑ > 1, the test plant (i.e., rosemary) was relatively susceptible, but when rsɑ < 1, the test plant was relatively resistant. Inoculation with M. enterolobii on rosemary/tomato resulted in rsɑ = 0.16, M. incognita rsɑ = 0.37 and M. javanica rsɑ = 0.16. The infection by M. javanica slightly affected the relative accumulation of Mg nutrient element in leaf tissues of rosemary. In conclusion, rsɑ values on rosemary were less than unity, suggesting that rosemary was relatively resistant to the three test Meloidogyne species.
Thesis (M.Sc. (Plant production)) -- University of Limpopo, 2023
Keywords: Tropical root-knot nematodes; Meloidogyne species; Nematode resistance; Plant nematodes; Root-knot nematodes; Nematode diseases of plants; Rosemary